Synthesis of design operation and management of surface irrigation conveyance systems - Sritharan, Subramaniaiyer, author; Richardson, E. V., advisor; Clyma, Wayne, advisor; Fontane, Darrell G., committee member; Sunada, Daniel K., committee member; Hall, W. A., committee member (Colorado State University. Libraries, 1984)
A theory for the design of conveyance systems, synthesizing with it the operation and management and set in an interdisciplinary mode is proposed. The theory involving eleven steps is required in the development of solutions to six basic problems hitherto inadequately addressed. These solutions are given in the following six modules of the dissertation: (i) Optimal Turnout Area Module, (ii) Turnout Area Water Requirement Module, (iii) Project Scale Farm Design Module, (iv) Ground Water Interaction Module, (v) Water Issue Strategy Module and (vi) Hydraulic Simulation Module. The problem of optimal turnout area was studied using causal processes theory (of mathematical sociology). Independence models and first order Markovian dependence models describing farmer behavior in the turnout area were studied. The turnout area water requirement problem was studied using a probability based design evapotranspiration computation procedure. Requirement depths were obtained by deriving optimal scheduling in space and time applying dynamic programming, using recent crop production functions and considering recent soil moisture stress models. Water requirements in terms of depth were converted to flow requirements in an optimal manner considering the hydraulics of the application system again using a two stage programming approach. Requirement efficiency and deep percolation ratio functions were developed for level borders using a zero-inertia model for four different soil types and for furrows using SCS approaches for the use in the model. Ground water interactions in the irrigated areas were studied using a linearized Boussinesq equation and Green's Function approach. Recharge excitation was represented by a finite Fourier series fitted to the excitations obtained using the developed deep percolation functions and the appropriate boundary conditions. Long term water table build up was studied using this approach for any detrimental effects due to application system design. Different water issue strategies and their optimality/acceptability were studied. The optimal strategy for a Rotational Water Issue (RWI) was that the rotations be as low in the hierarchy of the canal system as possible and the capacities depended on the irrigation intervals. The problem of hydraulic simulation was studied using the linearized diffusive wave equation for canal flow. The integral method was found to compare well with the analytical solution and was used for the solution of the advance problem. Delay times in releasing fixed steps of flow were computed using this approach. The operational criteria and necessary control measures were developed. The solution procedures were applied to a sample hypothetical project area and found to be applicable.
Covers not scanned.
Keywords: Irrigation engineering; Systems engineering